Hip screening in newborns in the UK: what are the latest guidelines?. (2nd October 2021) - Newton, Ayla C; Bohatschek, Marion; Rehm, Andreas; Ashby, Elizabeth
Abstract : The Newborn and Infant Physical Examination screening is a national screening programme which aims to identify infants with congenital abnormalities to minimise the risk of long-term complications. It involves a top to toe examination with special focus on the heart, eyes, testes and hips. The hip component of the Newborn and Infant Physical Examination screen aims to pick up infants with developmental dysplasia of the hips and refer them for appropriate treatment in a timely manner. Guidelines for the hip section of have recently changed. This article reviews these changes, the timings of the follow up and investigations, and the diagnosis and management of developmental dysplasia of the hips.